Comparison of Two Methods for Counting Molds in Fermentations Using the Production of Bikaverin by Fusarium oxysporum CCT7620 as a Model - dos Santos, Marcela Colombo; da Silva, Wesley Santiago; da Silva, Bianca Ferreira [UNESP]; Cerri, Marcel Otavio [UNESP]; Ribeiro, Marcelo Perencin de Arruda; Bicas, Juliano Lemos (Springer Nature, 2020)
The dry cell weight (DCW) measurement is one of the preferred methods to determine the growth of filamentous fungi. However, this technique is not applicable to insoluble culture media, besides being possibly influenced by the presence of extracellular biomass. The standard plate counting (SPC) is a reference method for detecting viable cells; however, it is referred as imprecise. In this study, we did a comprehensive analysis of the errors associated to each procedure and also determined the growth kinetics of Fusarium oxysporum in soluble (DCW and SPC) and insoluble (SPC) culture media. Finally, we used the production of bikaverin in airlift bioreactor containing insoluble medium as a case study to estimate red pigment production and to monitor biomass growth via SPC. We concluded that SPC can be used to give reliable fungal growth kinetics in media with insoluble matter, yielding errors equivalent to DCW depending on the number of replicates done for serial dilutions and plate counting.